Patellar Tendinopathy: Critical Analysis Review of Current Nonoperative Treatments. Issue 3 (8th March 2022) - Marigi, Erick M.; Buckley, Patrick; Razi, Farzad; Abbas, Muhammad J.; Jildeh, Toufic R.; Camp, Christopher L.; Krych, Aaron J.; Okoroha, Kelechi R.
Abstract : » Patellar tendinopathy is an attritional injury of the patellar tendon that is frequently identified in jumping athletes. Through repetitive or explosive movements, considerable loads and high peak strains are generated across the patellar tendon. » This leads to microinjury of tendon fibers, local mucoid degeneration, and loss of the fibrocartilaginous tissue that attaches tendon to bone. » Management of patellar tendinopathy often begins with nonoperative modalities: progressive tendon loading and eccentric rehabilitative exercise programs are the most effective. While a variety of additional treatment modalities are available, the comparative efficacy of these supportive treatments is not well differentiated at this time. » In this article, we analyze the existing literature regarding nonoperative treatment of patellar tendinopathy and provide additional insight on the effectiveness of current modalities.